Adult education as a common good: conceptualisation and measurement. Issue 3 (4th May 2018) - Boyadjieva, Pepka; Ilieva-Trichkova, Petya
ABSTRACT: The article outlines a theoretical framework for conceptualising adult education – and more broadly, lifelong learning – as a common good. It argues that the extent to which adult education as a common good is accomplished in a given society/country reflects its accessibility, availability, affordability and the social commitment to its functioning and that it depends on a country's specific institutional arrangements. Building on this conceptualisation and using data from the Adult Education Survey (AES), the Labour Force Survey (LFS) and the Continuing Vocational Training Survey (CVTS) for 24 European countries, the authors develop a composite index, based on these four dimensions, which measures the extent to which adult education as a common good is practiced in a given country. This index can be used to assess the effectiveness of national policies in the sphere of adult education across Europe. The results indicate substantial cross-country differences, with North European states and Luxembourg scoring best and Romania scoring worst. Finally, applying cluster analysis, the article identifies six distinctive clusters of countries with regard to the extent of adult education as a common good; the authors designate these cluster categories as reality, feasible, ambiguous, problematic, possible and invisible.